I'm going home. And now?" The difficult art of the Kangaroo Method at home - Mayara Carolina Cañedo; Cristina Brandt Nunes; Maria Aparecida Munhoz Gaiva; Ana Cláudia Garcia Vieira; Iluska Lopes Schultz (Universidade Federal de Santa Maria, 2021)
Objective: to get to know the parents' experience in applying the Kangaroo Mother Care at home. Method: qualitative research with data obtained between March and December 2016, by means of interviews with 12 mothers and three fathers of preterm and/or low-birth-weight newborns, participants in the third stage of the Kangaroo Method. The interviews were submitted to thematic content analysis technique. Results: the parents maintained the kangaroo position at home. Although each family developed it differently, they have not failed to implement it. They were also able to adapt to the new care routine with the arrival of the child at home and reported satisfaction with the medical appointments of the third stage and the follow-up carried out at the hospital. Conclusion: the parents, despite the daily challenges with home care, have a clear meaning about the importance of the Kangaroo Position for preterm and / or low-birth-weight newborns and its ability to affect the quality of care offered.